Analisis Yuridis Perjanjian Bisnis Franchise Terhadap Mitra Usaha Es Teh Nusantara - Mei Laudina Qomala Ashari; Yudhi Setiawan (Departement Business Law, Faculty of Law, University of Mataram, 2025)
The purpose of the study is to analyze how the implementation of franchise business agreements and ensure whether a fair and mutually beneficial agreement has been realized. This is regarding the rights and obligations between the franchisor and franchisee. Another purpose of the study is to find out how to resolve it if there is a unilateral termination by the franchisor. This study is an Empirical Normative Legal Research. In its implementation, the franchise business t is based on a franchise agreement. In this case, the franchisor and franchisee here have met the requirements for a valid agreement, namely the agreement of the parties, the competence of the parties, a certain thing, and a lawful cause. Settlement of disputes arising from unilateral termination by the franchisor in the Es Teh Nusantara franchise business agreement has been regulated in the Es Teh Nusantara cooperation agreement contract in Article 11. It concerns Dispute Settlement which states that the parties will be carried out by deliberation or mutual consensus resolution. However, if these efforts do not produce a solution, then both parties can use the settlement through Litigation (Court) which will be decided by The Court Decision. Keywords: Franchise Agreement, Termination